P13.06 Knowledge translation: development of a sexual health clinical audit tool to enhance adherence to evidence-based guidelines. (13th September 2015) - Nattabi, B; Kanai, S; Ferguson-Hill, S; Mosca, D; Murphy, M; Bailie, R
Abstract : Introduction: Sexually transmitted infections remain a significant public health issue for Indigenous Australians. Reasons for the high burden of disease include lack of access to quality care particularly in rural and remote Australia. Commissioned by the ABCD National Research Partnership, this project aimed to develop an audit tool to be used within a continuous quality improvement approach to enhance adherence to best-practice guidelines and improve the quality of Indigenous primary sexual health services. Methods: The process of development of the tool involved engagement of a range of stakeholders including clinical experts, quality improvement practitioners and researchers; identification and review of best practice guidelines; development of key indicators that reflect quality of care; generation of audit items and questions; and construction of the tool, protocol and report. The tool was piloted in Western Australia, Northern Territory, Queensland and South Australia. Results: The sexual health tool includes indicators that cover the basic elements of sexual health care including risk assessment, investigations, treatment, contact tracing and follow up. The protocol guides the use of the tool and the tailored report assists in identification of gaps, goal setting and planning of actions for improvement. Important elements of tool development are broad end user engagement, multidisciplinary and multi-jurisdictional consultation, effective leadership, sufficient resources and consensus building around selection of key elements of sexual health care. Conclusion: The tool, which reflects the best practice for Indigenous primary sexual healthcare, is now available to Indigenous primary health care services through the National Centre for Quality Improvement in Indigenous Primary Health Care (One21seventy). Used in conjunction with the systems assessment tool, the tool will be used to identify evidence-practice gaps, determine systems–related facilitators and barriers to quality care enhance the quality of sexual health care delivered to, and ultimately reduce the burden of STIs among, Indigenous Australians. Disclosure of interest statement: Barbara Nattabi is supported by an NHMRC Early Career Research Fellowship #1072777. Development of the tool was supported by the Lowitja Institute. No pharmaceutical grants were received in the development of this study.